Vegetation ecology - Franklin, Janet , 1959-; Maarel, E. van der (Wiley-Blackwell, 2013)
Written by leading experts from four continents, this up-to-date, innovative text takes an integrated multidisciplinary approach in presenting a comprehensive account of the composition, structure, ecology, diversity, distribution, and dynamics of plant communities and their environments